A Multidisciplinary Approach to Malocclusion Caused by Facial Multiple Fracture. (3rd March 2022) - Arai, Daishi; Yasue, Akihiro; Horiuchi, Shinya; Tanaka, Eiji
Abstract : In the case of multiple facial fractures, a simple open reduction occasionally causes various disorders during healing process after the surgery. Moreover, esthetic disturbance of a facial deformity might be induced. Therefore, the acquisition of facial symmetry and the recovery of occlusal and masticatory functions become increasingly important. This case report presents a successful treatment of facial multiple fracture induced by a car accident. A 20-year-old male was diagnosed with suffered multiple midface and mandibular fractures induced by a car accident. Midface fractures included the LeFort I and II type fractures, as well as sagittal fracture at midline and fractures from right maxillary sinus anterior wall to orbital wall. In the mandible, midline and left body fractures were detected. The patient underwent open reduction and rigid fixation of the fractured left zygoma, comminuted LeFort I and II fractures, and midline and left body of the mandible with intermaxillary fixation by multibracket appliance; maxillary osteotomy with iliac bone grafting; orthognathic two-jaw surgery with coronoid process grafts onto the depressed zygoma; and onlay graft of hydroxyapatite block on mandible. As the result, the multidisciplinary treatments successfully recover functions and esthetics to the satisfactory level of the patient with multiple facial fractures. As treatments for multiple facial fractures are required complexity due to the extent of trauma, multidisciplinary approach under the close cooperation between hospital departments is thought to be important.